The improvement of the normative providing of nuclear power plants pipelines systems saferty - Kiporenko, A. S.; Trich, R. M. (Національний технічний університет "Харківський політехнічний інститут", 2011)
Offered to recommendation on the improvement of the operating safety normative providing of the pipeline systems of the power plants. On the basis of the conducted researches an algorithm is offered on determination of resource of the pipeline systems taking into account different technical parameters.

Запропоновані рекомендації по удосконаленню нормативного забезпечення експлуатаційної безпеки трубопровідних систем атомних станцій. На основі проведених досліджень запропоновано алгоритм визначення ресурсу трубопровідних систем з врахуванням різних технічних параметрів.
Вдосконалення нормативного забезпечення безпечної експлуатації трубопровідних систем атомних станцій
Keywords: energyblocks; electricity production; technical parameters; physical-mechanical characteristics